Book Review: Vocational Education and Training in Times of Economic Crisis - Freund, Larissa; Gessler, Michael (International Journal for Research in Vocational Education and Training, 2017)
The book was published in the series "Technical and Vocational Education and Training: Issues, Concerns and Prospects". Series Editor-in-Chief is Rupert MacLean. Editor of the volume is Matthias Pilz, professor and holder of the chair of Economic and Business Education and director of the German Research Center for Comparative Vocational Education and Training (G.R.E.A.T) at the University of Cologne in Germany.